Public Access: Supporting Digital Inclusion for All: Maximising The Impact of Information and Communication Technologies (ICTs) For Inclusive Social And Economic Development - APC; IFLA; TASCHA (Technology & Social Change Group, 2014)
TASCHA, along with the Association for Progressive Communications (APC) and the International Federation of Library Associations & Institutions (IFLA) have prepared a briefing paper “Public access: Supporting digital inclusion for all – Maximising the impact of information and communication technologies (ICTs) for inclusive social and economic development”. The paper was produced for the Commission on Science and Technology for Development (CSTD), Seventeenth Session which IFLA attended between 2-16 May 2014 in Geneva. The briefing paper draws UN Member States' attention to the importance of access to ICTs as a key issue in development and to the ongoing digital divide. It includes a checklist of action points for policymakers that highlights an ecosystem approach to ensure better public access.
Keywords: libraries; public access; public access ICTs; ICT4D; ICTD; telecenters; cybercafes; development; international development; policy; UN; post-2015